Heavy Metal Contamination and Ecological Risk Assessment in the Soil of Tannery Industry at Savar (Chemical Engineering Research Bulletin, 2021)
Heavy metal contamination in soil is considered a global crisis and its bulk proportion are in developing countries like Bangladesh. Five heavy metals such as Cd, Cr, Pb, Cu and Ni were investigated in the soil of Savar tannery industrial estate. The decreasing trend of metals was observed in soil as Cr>Cu>Ni>Pb>Cd. According to US EPA guideline, Cr was heavily polluted at the selected locations. Cu was highly polluted, whereas Cd and Pb were not polluted and Ni was moderately polluted. On the basis of Pearson’s correlation Cd-Pb, Cd-Cu, Cu-Ni, Ni-Cu, Ni-Pb were significantly correlated. From the pollution index, metal pollution of sediments was found in the order as Cr>Cu>Pb>Cd. Degree of contamination and modified degree of contamination were higher in the dumping zones. The geo-accumulation index for Cr showed moderate to extremely contaminated. Ecological risk arrayed in the order of Cr>Cu>Ni>Pb>Cd in the soil of study area. Geographic information system (GIS) was also used to map the spatial distribution of heavy metal contamination in the soil. This study recommended that continuous monitoring of heavy metal contamination should be directed to assess their risk in the soil of tannery industry at Savar.Chemical Engineering Research Bulletin 21(2020) 106-113